Impact of olfactory function on the trajectory of cognition, motor function, and quality of life in Parkinson’s disease - Lin, Chia-Yen; Tsai, Yu-Shan; Chang, Ming-Hong (Frontiers in Aging Neuroscience, 2024)
Background Olfactory dysfunction in Parkinson’s disease (PD) is associated with more severe phenotypes, but trajectories of cognitive function, disease severity, and subdomains of quality-of-life measurements in patients with distinct olfactory profiles remain underexplored. Objective To analyze the influence of olfaction on trajectories of clinical parameters in patients with PD. Design Retrospective cohort study. Subjects From October 2016 to May 2021, the study tracked 58 participants over 3 years. Participants completed follow-up assessments using tools including the Chinese version of the University of Pennsylvania’s Smell Identification Test (UPSIT), Montreal Cognitive Assessment (MoCA), Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale, and the Chinese translation of the 39-item Parkinson’s Disease Questionnaire (PDQ-39). Methods Participants were divided into anosmia (UPSIT < 19) and non-anosmia (UPSIT ≥ 19) groups based on initial scores. Generalized estimating equations and repeated measures correlations were used to examine longitudinal associations and correlations between olfaction and clinical parameters. Results Divergent cognitive trajectories were observed between groups. The anosmia group exhibited a faster cognitive decline (adjusted B [beta coefficient] = −1.8, p = 0.012) according to the interaction effect of olfaction and time on the MoCA score. The anosmia group exhibited no longitudinal correlation between cognition and olfactory function but showed correlations with age (rrm [coefficient of repeated measures correlation] = −0.464, p = 0.004) and disease duration (rrm = −0.457, p = 0.005). The non-anosmia group’s UPSIT scores decreased over time (B = −2.3, p = 0.005) alongside a significant correlation with motor function (rrm = −0.479, p = 0.006). Conclusion The anosmia group’s accelerated cognitive decline correlated with age and disease duration, but not olfactory function, suggesting a poor cognitive outcome in this population despite the lack of longitudinal correlation between cognition and olfaction. The non-anosmia group exhibited progressive olfactory degradation and notable correlations between motor function and UPSIT scores, implying pathological accumulation in the olfactory structure and basal ganglia.